DETERMINATION OF HYDROGEN PEROXIDE IN SNOW : PRELIMINARY RESULTS FOR SNOW SAMPLES IN THE INLAND REGION, ANTARCTICA - カミヤマ, コキチ; ナカヤマ, エイイチロウ; KAMIYAMA, Kokichi; NAKAYAMA, Eiichiro (National Institute of Polar Research, 1992)
P(論文) Hydrogen peroxide (H_2O_2) in snow possibly marks annual layers of snow deposition as well as the atmospheric environments where it is created. Methods for the determination of H_2O_2 in snow and their suitability for field observation are discussed. The vertical plate of a surface snow block obtained on the inland high plateau, Antarctica, (point γ-8) was analyzed to precisely determine H_2O_2 distribution. Relatively high concentrations of H_2O_2 were detected, suggesting seasonal fluctuation. Laminated snow layers of glaciers record past depositional environments. Sufficiently fine sampling intervals of snow, both horizontally (geographically) and vertically, are important to make clear the depositional environments over the glaciers. The in situ measurements of some of the chemical constituents in snow will help us to determine the appropriate sampling intervals, as well as to avoid the possibility of contamination. The other analytical results, obtained later in the laboratory experiments, are increased in value by the fine sampling intervals. departmental bulletin paper